Podcast
Questions and Answers
In the linear equation ax + b = 0, after moving the constant term to the right side, the equation becomes $ax = ______$
In the linear equation ax + b = 0, after moving the constant term to the right side, the equation becomes $ax = ______$
-b
After dividing both sides of the equation ax = -b by 'a', the equation becomes $x = ______$
After dividing both sides of the equation ax = -b by 'a', the equation becomes $x = ______$
-b / a
In the equation 3x + 5 = 0, after moving the constant term to the right side, the equation becomes $3x = ______$
In the equation 3x + 5 = 0, after moving the constant term to the right side, the equation becomes $3x = ______$
-5
After dividing both sides of the equation 3x = -5 by 3, the equation becomes $x = ______$
After dividing both sides of the equation 3x = -5 by 3, the equation becomes $x = ______$
In the equation ax + bx = cx + d, after combining like terms, the equation becomes $(a + b)x = ______$
In the equation ax + bx = cx + d, after combining like terms, the equation becomes $(a + b)x = ______$
If the given linear equation has multiples of 'x' on both sides, that is, ax + bx = cx + d, you can proceed by replacing ax + bx = cx + d with $(a + b)x = ______$
If the given linear equation has multiples of 'x' on both sides, that is, ax + bx = cx + d, you can proceed by replacing ax + bx = cx + d with $(a + b)x = ______$
Step 2: Move the constant term (______
) to the right side of the equation. Replace (a + b)x = ______
with (a + b)x = -\left(______\right)
.
Step 2: Move the constant term (______
) to the right side of the equation. Replace (a + b)x = ______
with (a + b)x = -\left(______\right)
.
Step 3: Divide both sides of the equation by ______
. Replace ______x = -\left(c + d\right)
with x = -\frac{\left(c + d\right)}{\left(a + b\right)}
.
Step 3: Divide both sides of the equation by ______
. Replace ______x = -\left(c + d\right)
with x = -\frac{\left(c + d\right)}{\left(a + b\right)}
.
Step 4: Answer the question "What is the value of x
." Substitute the value of ______
and -(c + d)
into the expression for x
. For example, consider the equation 2x^2 + 3x = 5x - 4
. 1. Combine like terms: 2x^2 + 3x = 5x - 4
becomes x^2 + 3x = 5x - 4
.
Step 4: Answer the question "What is the value of x
." Substitute the value of ______
and -(c + d)
into the expression for x
. For example, consider the equation 2x^2 + 3x = 5x - 4
. 1. Combine like terms: 2x^2 + 3x = 5x - 4
becomes x^2 + 3x = 5x - 4
.
Step 2: Move the constant term (______
) to the right side of the equation. Replace ax^2 + bx = cx^2 + d
with ax^2 + bx = -\left(______\right)
.
Step 2: Move the constant term (______
) to the right side of the equation. Replace ax^2 + bx = cx^2 + d
with ax^2 + bx = -\left(______\right)
.
Step 3: Divide both sides of the equation by ______
. Replace ax^2 + bx = -\left(c + d\right)
with x^2 = -\frac{\left(c + d\right)}{\left(a + b\right)}
.
Step 3: Divide both sides of the equation by ______
. Replace ax^2 + bx = -\left(c + d\right)
with x^2 = -\frac{\left(c + d\right)}{\left(a + b\right)}
.
Step 4: Answer the question "What is the value of x^2
." Substitute the value of ______
and -(c + d)
into the expression for x^2
. For example, consider the equation 2x^2 + 3x = 5x^2 - 4
. 1. Combine like terms: 2x^2 + 3x = 5x^2 - 4
becomes 3x^2 = 2x - 4
.
Step 4: Answer the question "What is the value of x^2
." Substitute the value of ______
and -(c + d)
into the expression for x^2
. For example, consider the equation 2x^2 + 3x = 5x^2 - 4
. 1. Combine like terms: 2x^2 + 3x = 5x^2 - 4
becomes 3x^2 = 2x - 4
.
Step 2: Move the constant term (______
) to the right side of the equation.
Step 2: Move the constant term (______
) to the right side of the equation.
Step 1: Combine like terms. Replace ______ = cx^3 + d
with (a + b)x^2 = c + d
.
Step 1: Combine like terms. Replace ______ = cx^3 + d
with (a + b)x^2 = c + d
.
Step 2: Move the constant term (______
) to the right side of the equation.
Step 2: Move the constant term (______
) to the right side of the equation.
What is the value of x^2
? Substitute the value of ______
and -(c + d)
into the expression for x^2
.
What is the value of x^2
? Substitute the value of ______
and -(c + d)
into the expression for x^2
.
Flashcards
Linear equation
Linear equation
An equation where the highest power of the variable is 1, represented as ax + b = 0, where a and b are constants and x is the variable.
Solving a linear equation
Solving a linear equation
The process of finding the value of the variable (x) that makes the equation true.
Step 1: Move the constant
Step 1: Move the constant
The first step in solving a linear equation involves moving the constant term (b) to the right side of the equation.
Step 2: Divide by the coefficient
Step 2: Divide by the coefficient
Signup and view all the flashcards
Step 3: Find the value of x
Step 3: Find the value of x
Signup and view all the flashcards
Linear equation with multiples of x
Linear equation with multiples of x
Signup and view all the flashcards
Step 1: Combine like terms
Step 1: Combine like terms
Signup and view all the flashcards
Step 2: Move the constant
Step 2: Move the constant
Signup and view all the flashcards
Step 3: Divide by the combined coefficient
Step 3: Divide by the combined coefficient
Signup and view all the flashcards
Step 4: Find the value of x
Step 4: Find the value of x
Signup and view all the flashcards
Linear equation with multiples of x^2
Linear equation with multiples of x^2
Signup and view all the flashcards
Step 1: Combine like terms
Step 1: Combine like terms
Signup and view all the flashcards
Step 2: Move the constant
Step 2: Move the constant
Signup and view all the flashcards
Step 3: Divide by the combined coefficient
Step 3: Divide by the combined coefficient
Signup and view all the flashcards
Step 4: Find the value of x^2
Step 4: Find the value of x^2
Signup and view all the flashcards
Linear equation with multiples of x^3
Linear equation with multiples of x^3
Signup and view all the flashcards
Study Notes
Solving Linear Equations
Linear equations play a fundamental role in mathematics as they are used to represent relationships between two variables. These equations can be written in the form ax + b = 0
, where a
and b
are constants, and x
is the variable. In this section, we will discuss how to solve linear equations for x
.
The Basic Process for Solving Linear Equations
-
Step 1: Move the constant term (
b
) to the right side of the equation.Replace the original equation
ax + b = 0
withax = -b
. -
Step 2: Divide both sides of the equation by
a
.Replace
ax = -b
withx = -b / a
. -
Step 3: Answer the question "What is the value of
x
?"Substitute the value of
a
andb
from the original equation into the expression forx
.
For example, consider the equation 3x + 5 = 0
.
- Move the constant term (
5
) to the right side of the equation:3x = -5
. - Divide both sides by
3
:x = -5 / 3
. - Substitute the values of
a
andb
into the expression forx
:x = -5 / 3
.
The value of x
is -5 / 3
.
Solving Linear Equations with Multiples of x
on Both Sides
If the given linear equation has multiples of x
on both sides, that is, ax + bx = cx + d
, you can proceed as follows:
-
Step 1: Combine like terms.
Replace
ax + bx = cx + d
with(a + b)x = c + d
. -
Step 2: Move the constant term (
c + d
) to the right side of the equation.Replace
(a + b)x = c + d
with(a + b)x = -(c + d)
. -
Step 3: Divide both sides of the equation by
(a + b)
.Replace
(a + b)x = -(c + d)
withx = -(c + d) / (a + b)
. -
Step 4: Answer the question "What is the value of
x
?"Substitute the value of
(a + b)
and-(c + d)
into the expression forx
.
For example, consider the equation 2x^2 + 3x = 5x - 4
.
- Combine like terms:
2x^2 + 3x = 5x - 4
becomesx^2 + 3x = 5x - 4
. - Move the constant term (
5x - 4
) to the right side of the equation:x^2 + 3x = -(5x - 4)
. - Divide both sides by
(1 + 3)
:x = -(5x - 4) / (1 + 3) = -(5x - 4) / 4
. - Substitute the values of
(1 + 3)
and-(5x - 4)
into the expression forx
:x = -(5x - 4) / 4
.
The value of x
is -(5x - 4) / 4
.
Solving Linear Equations with Multiples of x^2
on Both Sides
If the given linear equation has multiples of x^2
on both sides, that is, ax^2 + bx = cx^2 + d
, you can proceed as follows:
-
Step 1: Combine like terms.
Replace
ax^2 + bx = cx^2 + d
with(a + b)x^2 = c + d
. -
Step 2: Move the constant term (
c + d
) to the right side of the equation.Replace
(a + b)x^2 = c + d
with(a + b)x^2 = -(c + d)
. -
Step 3: Divide both sides of the equation by
(a + b)
.Replace
(a + b)x^2 = -(c + d)
withx^2 = -(c + d) / (a + b)
. -
Step 4: Answer the question "What is the value of
x^2
?"Substitute the value of
(a + b)
and-(c + d)
into the expression forx^2
.
For example, consider the equation 2x^2 + 3x = 5x^2 - 4
.
- Combine like terms:
2x^2 + 3x = 5x^2 - 4
becomes3x^2 = 2x - 4
. - Move the constant term (
2x - 4
) to the right side of the equation:3x^2 = -(2x - 4)
. - Divide both sides by
3
:x^2 = -(2x - 4) / 3
. - Substitute the values of
3
and-(2x - 4)
into the expression forx^2
:x^2 = -(2x - 4) / 3
.
The value of x^2
is -(2x - 4) / 3
.
Solving Linear Equations with Multiples of x^3
on Both Sides
If the given linear equation has multiples of x^3
on both sides, that is, ax^3 + bx^2 = cx^3 + d
, you can proceed as follows:
-
Step 1: Combine like terms.
Replace
ax^3 + bx^2 = cx^3 + d
with(a + b)x^2 = c + d
. -
Step 2: Move the constant term (
c + d
) to the right side of the equation.
Studying That Suits You
Use AI to generate personalized quizzes and flashcards to suit your learning preferences.
Description
Learn about the basic process for solving linear equations and how to handle equations with multiples of x, x^2, or x^3 on both sides. Practice solving linear equations step by step with examples.